2015
DOI: 10.1021/acschemneuro.5b00186
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Real-Time Monitoring of Glutathione Redox Status in Single Pyramidal Neurons in Organotypic Hippocampal Slices during Oxygen–Glucose Deprivation and Reperfusion

Abstract: A redox-sensitive Grx1-roGFP2 fusion protein was introduced by transfection into single pyramidal neurons in the CA1 subfield of organotypic hippocampal slice cultures (OHSCs). We assessed changes in the GSH system in neuronal cytoplasm and mitochondria during oxygen-glucose deprivation and reperfusion (OGD/RP), an in vitro model of stroke. Pyramidal cells in a narrow range of depths below the surface of the OHSC were transfected by gene gun or single-cell electroporation with cyto- or mito-Grx1-roGFP2. To mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 95 publications
0
25
0
Order By: Relevance
“…We have specifically designed our investigations to minimize the likelihood that transcription/translation are responsible for the observed effects. We improved the OGD-RP procedure to switch solutions rapidly (70) so that ROS changes could be measured within a few minutes. We restricted our attention to pyramidal cells, but did not isolate them, thus allowing the natural interaction between glia and neurons to occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have specifically designed our investigations to minimize the likelihood that transcription/translation are responsible for the observed effects. We improved the OGD-RP procedure to switch solutions rapidly (70) so that ROS changes could be measured within a few minutes. We restricted our attention to pyramidal cells, but did not isolate them, thus allowing the natural interaction between glia and neurons to occur.…”
Section: Discussionmentioning
confidence: 99%
“…pCMV-tdTomato (Clontech) and pCS2+ (Addgene) were kindly provided by Zachary P. Wills (University of Pittsburgh). pMito-tdTomato was constructed in the Deiters laboratory (University of Pittsburgh) (70). The antibodies and dye used in WBs and IF are listed in Supplementary Data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many fewer studies have attempted to exploit genetically encoded sensors for the real-time evaluation of alterations in cell signaling and metabolism in in vitro models of brain hypoxic injury. For instance, the responses of the glutathione redox system in neuronal cytoplasm and mitochondria during the course of oxygen-glucose deprivation and reperfusion in organotypic brain slices (an in vitro model of the stroke) were recorded by using the genetically encoded fusion biosensor Grx1-roGFP2 [276]. Under precisely controlled treatment conditions within a sample, the fluorescence signal from the biosensor was accurately calibrated using a signal from the co-transfected fluorescent protein tdTomato as an internal standard.…”
Section: In Vitro Models For Real-time Imaging Of Cell Signaling and mentioning
confidence: 99%
“…The latter allowed for the quantitative determination of the reduction potential of the glutathione system in the neuronal cytoplasm and mitochondria during the course of oxygen-glucose deprivation and reperfusion. Using their improved protocol, the authors were able to define time dependence of the redox state of the glutathione system in this in vitro model of the stroke [276]. Moreover, they demonstrated that the mitochondrial reduction potential became more reducing during oxygen-glucose deprivation and more oxidizing during reperfusion, while the cytoplasmic reduction potential did not change significantly.…”
Section: In Vitro Models For Real-time Imaging Of Cell Signaling and mentioning
confidence: 99%